LOCAL DRUG DELIVERY IN THE TREATMENT OF ORAL LICHEN PLANUS: A SYSTEMATIC REVIEW - SHOVNA SHIVANI MISHRA,; T.N. UMA MAHESWARI, (International Journal of Pharma and Bio Sciences, 2014)
Oral lichen planus (OLP) is a chronic, mucocutaneous, inflammatory disease characterized by cell-mediated immune dysfunction. The oral cavity has proven to be a potential topical delivery site for local delivery of therapeutic agents. This paper aims to analyze the existing literature on the local drug delivery in the treatment of oral lichen planus. Electronic search of scientific papers was carried out to identify relevant articles. Results revealed a review paper on the local drug delivery for treatment of oral lichen planus, a case report where two cases of erosive lichen planus were treated with Clobetasol propionate in custom-fitted tray, a randomized control trial where a new mucoadhesive prolonged release tablet containing Clobetasol propionate was used for the management of oral lichen planus. The potential for local delivery systems in oral lichen planus hasn’t yet been fully realized and further research is needed in order to improve treatment outcomes.